Fuzzy Sets and Operations Research - Cao, Bing-Yuan.; Zhong, Yu-Bin.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the latest advances in applying fuzzy sets and operations research technology and methods. It is the first fuzzy mathematics textbook for students in high school and technical secondary schools. Part of Springer's book series: Advances in Intelligent and Soft Computing, it includes the 36 best papers from the Ninth International Conference on Fuzzy Information and Engineering (ICFIE2017), organized by the Fuzzy Information and Engineering Branch of Operations Research Society of China and Operations Research Society of Guangdong Province in China. Every paper has been carefully peer-reviewed by leading experts. The areas covered include 1. Fuzzy Measure and Integral; 2. Fuzzy Topology and Algebras; 3. Classification and Recognition; 4. Control and Fuzziness; 5. Extension of Fuzzy Set and System; 6. Operations Research and Management (OR); The book is suitable for college, masters and doctoral students; educators in universities, colleges, middle and primary schools teaching mathematics, fuzzy sets and systems, operations research, information and engineering, as well as management, control. Discussing case applications, it is also a valuable reference resource for professionals interested in theoretical and practical research.
Trapezoidal Intuitionistic Approximations of Intuitionistic Fuzzy Numbers Preserving the Ambiguity -- New Deﬁnition of the Deﬁnite Integral of Fuzzy Valued Function Linearly Generated by Structural Elements -- An information quantity-based uncertainty measure to incomplete numerical systems -- An Inexact Reasoning Method Based on Sugeno Integral -- Properties of fuzzy ﬁlters in EQ-algebras -- The (ε, ε ∨ q(λ, µ) )-fuzzy subalgebras of K U - algebras -- On derivations of FI-algebras -- A New Type Soft Prime Ideal of K U -algebras -- On (ε, ε ∨ q(λ, µ))-fuzzy ideals of KU-algebras -- The equivalence between stratiﬁed L-neighborhood groups and stratiﬁed L-neighborhood topological groups -- On (ε, ε ∨ qk )-fuzzy Filters in R0 -algebras -- A Classiﬁcation Method by Using Fuzzy Neural Network and Ensemble Learning -- Power Load Pattern Classiﬁcation Based on Threshold and Cloud Improved Fuzzy Clustering -- The Centrality Analysis of the Fuzzy Technology Innovation Network -- Social Network User Feature Recognition Method Based on Weighted Graph and Fuzzy Set -- A new classiﬁer fusion algorithm and its application in practice -- Some results on conditionally subcancellative triangular subnorms -- The Semantic Information Method Compatible with Shannon, Popper, Fisher, and Zadehs Thoughts -- Regression Analysis for Connection Number via Deviation Transmission -- Research on Remote Control and Management Based on 4G Network" in Modern and High Efﬁciency Agriculture -- A Study of Intuitionistic Fuzzy Rough Sets -- On the characterizations of L-fuzzy rough sets based on fuzzy lattices -- Trigonometric Wavelet Methods for the Plane Elasticity Problem -- Study on Destruction Transformation of Error System Structure -- Interval Type-2 Fuzzy System based on NT method and Its Probability Representation -- Coordination of the supply chain with Nash bargaining fairness concerns -- Normality and shared values of meromorphic functions with differential polynomial -- Analysis of Error System Structure-Dynamic Structure and Static Structure -- Adaptive Synchronization Control of the Fractional Order Hyper Chaotic Systems with Unknown Parameters -- Pricing Problem on the Task of Making Money by Taking Photos -- Application of Fuzzy System Method in Economic Data Analysis -- A Interval Number Ranking Method Based on Interval Quantile and TOPSIS for Decision Problems -- Study on Rapidity Decision of Highway Lane Changing Based on OS-ELM -- Study of the Impact on Trafﬁc Capacity Made by Opening Block Type Housing Estates -- Discussion on Spread of Fuzzy Mathematics from Publication of Fuzzy Sets Theory Preliminary -- .
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence